(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aims to identify the concept of human capital, and the methodology for measuring it by relying on a composite evidence of eight sub-indicators represented by (average years of schooling, probability of death rate among adults per 1000 population, literacy rate among adult females, enrollment rate in university education, The quality of the education system, unemployment rate among university graduates, brain drain) to indicate the relative position of the Syrian Arab Republic among a sample of countries in terms of its human capital stock and the extent of benefiting from this stock during the period (1995-2004-1995). The study found that Syria possesses an average balance of its human capital compared to a sample of countries during the studied period.